A Validation Trajectory for the Washington Assessment of Risks and Needs of Students. Issue 1 (2nd January 2020) - Gotch, Chad M.; French, Brian F.
ABSTRACT: The State of Washington requires school districts to file court petitions on students with excessive unexcused absences. The Washington Assessment of Risks and Needs of Students (WARNS), a self-report screening instrument developed for use by high school and juvenile court personnel in such situations, purports to measure six facets of risks and needs of youth relevant to improving school and life outcomes. Many psychometric analyses have been documented either in the technical manual or through peer-reviewed publications. We review this body of evidence in the context of a central claim about score interpretation/use and the inferences that underlie that claim. Such evidence is strong for inferences related to the target domain, scoring, generalization, and extrapolation. Evidence for an implication inference, however, is pending. We propose a validation trajectory partnership for the WARNS to build evidence through a collaborative research program.